(untitled) (Proximus Journal of Sports Science and Physical Education, 2024)
This study examines the influence of contemporary technologies on the precision of measurement and assessment in rhythmic gymnastics. A total of 50 gymnasts from the College of Physical Education and Sports Sciences involved in the study were organised into five teams, each executing movements prior to and following the introduction of a new evaluation system in 2001, which raised the maximum score from 10 to 20 points. Advanced technical instruments, such as motion capture devices and artificial intelligence-driven assessment software, were employed to improve the precision of performance evaluation. The results indicated a notable enhancement in performance scores across all teams, with team “E” attaining the greatest rise in mean score from 7.9 (standard deviation = 0.3) prior to implementation to 16.3 (standard deviation = 1.0) subsequent to it. Statistical tests employing the (T) test demonstrated extremely significant changes (p < 0.05) in scores pre-and post-implementation of current technology across all teams, with “Cohen’s d” values ranging from 2.06 to 2.82, signifying large impact sizes. The ANOVA results indicated statistically significant differences across the teams (F(4, 45) = 4.65, p = 0.009, η² = 0.29). The regression study indicated that current technology accounted for 55% of the variance in performance outcomes (Adjusted R² = 0.55). The results affirm the vital importance of technology in improving the precision and impartiality of rhythmic gymnastics evaluations, indicating that the ongoing incorporation of these tools will be imperative for the advancement of the sport